An assessment of the role of buttress roots in the carbon stocks of tropical forests - Wang, Xu; Mwangi, Brian Njoroge; Zhou, Guangyi; Yang, Mengmeng; Li, Yuelin (Frontiers in Plant Science, 2025)
IntroductionAssessing carbon stocks in tropical forests is crucial for understanding their role in mitigating climate change. Researchers have previously underestimated key factors contributing to carbon dynamics in tropical forests. This study aims to address this knowledge gap.MethodsThis study collected soil samples and made physical measurements of buttressed, control, and non-buttressed trees in a tropical forest from 2020 to 2022. ResultsOur findings reveal that a significant proportion of trees (69.57%) had 3 to 5 buttress roots per tree. The total average biomass of the buttress roots and the above-ground portion of the trees with buttress roots was calculated to be 8.5 tonnes/ha for buttress roots and 44.04 tonnes/ha for above-ground biomass. The buttress root biomass accounted for 16.18% of the total tree biomass. It was observed that the presence of buttress roots was associated with a higher soil organic carbon content by an average of 20.8% in the upslope areas with buttress roots regardless of the season. Tree species with buttress roots had on average 20% higher organic carbon content. The upslope area of trees with buttress roots had lower soil temperature and higher soil moisture when compared to the other sectors measured in the study. Regardless of the season, the soil respiration rate in the areas without buttress roots and the control areas was higher than in those with buttress roots. The presence of buttress roots positively affected soil nutrient concentration throughout the study period.DiscussionThis research shows that buttress roots play a crucial role in carbon storage. By integrating buttress roots into carbon accounting models, we can obtain more accurate estimates of carbon stock potential and develop more effective conservation and restoration strategies for tropical forests.